Evolution of kinase polypharmacology across HSP90 drug discovery. Issue 10 (21st October 2021) - Antolin, Albert A.; Clarke, Paul A.; Collins, Ian; Workman, Paul; Al-Lazikani, Bissan
Summary: Most small molecules interact with several target proteins but this polypharmacology is seldom comprehensively investigated or explicitly exploited during drug discovery. Here, we use computational and experimental methods to identify and systematically characterize the kinase cross-pharmacology of representative HSP90 inhibitors. We demonstrate that the resorcinol clinical candidates ganetespib and, to a lesser extent, luminespib, display unique off-target kinase pharmacology as compared with other HSP90 inhibitors. We also demonstrate that polypharmacology evolved during the optimization to discover luminespib and that the hit, leads, and clinical candidate all have different polypharmacological profiles. We therefore recommend the computational and experimental characterization of polypharmacology earlier in drug discovery projects to unlock new multi-target drug design opportunities. Graphical abstract: Highlights: Characterization of kinase polypharmacology landscape for HSP90 inhibitors Ganetespib and luminespib display unique polypharmacology Kinase polypharmacology evolved during optimization to discover luminespib Earlier characterization of polypharmacology in drug discovery is recommended Abstract : Polypharmacology is seldom comprehensively investigated during drug discovery. Antolin et al. describe the identification of polypharmacology for two HSP90 inhibitors and how it evolved during the discovery of luminespib, highlighting the importance of characterizing polypharmacology earlier in drug discovery.